(untitled) (Research, Society and Development, 2020)
Food is the main factor for determining and establishing the culture of a people or an entire society, as it will define the eating behavior of that population through geography, that is, nature has no role in mapping food and how it take place throughout history, either through the biome or even in the influences of other peoples on cultural exchange through immigration. For the elaboration of this work, through field research, it was structured as qualitative research and through oral history and ethnography the application of interviews was used in order to map the food culture of the residents of Beberibe. The interviews resulted in reports of memories of what the interviewees’ food culture was like. The importance of this research aims to contribute scientifically both as a bibliographic collection in relation to the culture of a people and to highlight the social theme related to food and to be the basis of research in the area.